PTU-105 Preoperative ciclosporin therapy and appropriate steroid use does not increase risk of infective complications following colectomy for ulcerative colitis. (28th May 2012) - Krupa, L; Dave, P; Hart, A; Igali, L; Tighe, R; Tremelling, M
Abstract : Introduction: Corticosteroids increase the risk of serious and opportunistic infections, independently and in combination with immunosuppressives. Steroids increase risk of post operative sepsis OR 1.68 in Crohn's disease. 1 Addition of immunosuppressants in Crohn's increases the risk of opportunistic infection. 2 In acute severe ulcerative colitis (ASUC) addition of ciclosporin is standard management for patients not responding rapidly to IV steroids alone. Some patients do not respond and require urgent surgery. 3 The risk of preoperative ciclosporin therapy to postoperative complications is not known. Methods: We conducted a retrospective review of patients undergoing colectomy for UC in 2009–2010 in a large centre. 40 colectomies were identified: 26 for ASUC the remainder for cancer or steroid dependency. Differences in post operative complication rates for all 40 individuals were compared between those who received ciclosporin (cases) and those who did not (controls). Analysis was by logistic regression techniques within STATA correcting for steroid use pre and post operatively. Age, gender ASA grade and diabetes were included as potential confounders. Results: In our panel there was no increase in post operative wound infections, (OR 0.4, p=0.34) intra-abdominal sepsis (OR 1.32, p=0.74), non-GI serious infections (OR 1.9, p=0.39) or all sepsis (OR 0.47, p=0.29) in ciclosporin treated patients compared with controls. There was also no increase in complication rates in patients given high dose steroids before (OR 0.14, p=0.1) or after admission (OR 1.2, p=0.75). Neither steroid use nor ciclosporin use predicted thromboembolic or bleeding complications or need for HDU. Conclusion: Used appropriately in accordance with current guidelines 4 neither steroids nor ciclosporin increase the risk of post operative infective complications in patients failing medical therapy for ASUC. Competing interests: None declared. References: 1. Subramanian V . Am J Gastro 2008;103 :2373. 2. Toruner M . Gastro 2008;134 :929. 3. Van Assche G . Gastro 2003;125 :1025. 4. Travis S . J Crohn's Colitis 2008;2 :24.